2021
DOI: 10.1111/ijsa.12328
|View full text |Cite
|
Sign up to set email alerts
|

The Decent Work Questionnaire: Psychometric properties of the Italian version

Abstract: Decent work is an integrative concept that may account for several labor-related issues. It represents the defence and promotion of human rights at work and business and the fulfilling and productive work maintained with social dialogue. Previous studies developed the Decent Work Questionnaire based on International Labor Organization propositions and workers' perceptions.The paper reports the adaptation and validation of its Italian version in a high-skilled workers sample (N = 1,465). Confirmatory factor an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
1
9
0
1
Order By: Relevance
“…Ferraro's decent work notion which highlights individuals' perceptions of work by referring to the ILO's 11 substantive elements, has also been studied in conjunction with a wide variety of psychological phenomena, such as personal burnout, work engagement, thriving at work, and motivation, etc. (Ferraro et al, 2021 ; Sheng and Zhou, 2021 ; Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferraro's decent work notion which highlights individuals' perceptions of work by referring to the ILO's 11 substantive elements, has also been studied in conjunction with a wide variety of psychological phenomena, such as personal burnout, work engagement, thriving at work, and motivation, etc. (Ferraro et al, 2021 ; Sheng and Zhou, 2021 ; Xu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Decent work is perceived as the lever for expressing these four values by means of pursuing four strategic objectives: (1) standards and fundamental principles and rights at work, (2) employment, (3) social protection, and (4) social dialogue (International Labor Organization., 1999 ; International Labour Organization., 2008 ). Nowadays decent work has been promoted all over the world at theoretical, practical, and research levels (Pereira, 2019 ; Rantanen et al, 2020 ; Blustein et al, 2023 ) and applied to various population groups from high-skilled occupations (e.g., knowledge workers like college/university faculty members) to low-skilled ones (e.g., domestic workers) (D'Souza, 2010 ; Ferraro et al, 2021 ). Third, as a lens for informing a comprehensive review of working conditions, the decent work notion is conceptualized as a multidimensional concept encompassing various favorable or enabling working dimensions.…”
Section: Introductionmentioning
confidence: 99%
“…The DWQ (Ferraro et al , 2018b) measures DW dimensions of the work context and content considering workers’ perceptions. The questionnaire was already adapted and validated for Portuguese, Brazilian and Italian samples (Ferraro et al , 2018b; Ferraro et al , 2021). The DWQ is a 31-item scale that provides a Global DW score (second-order factor) with seven dimensions: Fundamental principles and values at work (with six items), measuring to what extent freedom, justice, non-discrimination, participation in decisions, respect and trust are present at work and related contexts (DW1; e.g.…”
Section: Methodsmentioning
confidence: 99%
“…One of the main steps in this strategy is to consider the theoretical basis of the model. Considering the instrument's previous validation history in Portugal, Brazil (Ferraro et al, 2018b) and Italy (Ferraro et al, 2021), we found the suggestion to test the higher-order model (HOM, Cred e and Harms, 2015). For comparison, we built this path diagram and two additional ones: one considering a one single-factor model (SFM, commonly the zero model; Model 4 in Table 2) and a third model using the seven DW factors (without the second-order factor) or the oblique-first-order model (OblFOM, Model 3 in Table 2).…”
Section: Competing Models Strategymentioning
confidence: 99%
See 1 more Smart Citation